"Please. Don't. Die.": A Grounded Theory Study of Bystander Cardiopulmonary Resuscitation. Issue 2 (February 2018) - Mausz, Justin; Snobelen, Paul; Tavares, Walter
Abstract : Background: Bystander cardiopulmonary resuscitation (CPR) is an important determinant of survival from out-of-hospital cardiac arrest (OHCA), yet rates of bystander CPR are highly variable. In an effort to promote bystander CPR, the procedure has been streamlined, and ultrashort teaching modalities have been introduced. CPR has been increasingly reconceptualized as simple, safe, and easy to perform; however, current methods of CPR instruction may not adequately prepare lay rescuers for the various logistical, conceptual, and emotional challenges of resuscitating a victim of cardiac arrest. Methods and Results: We adopted a constructivist grounded theory methodology to qualitatively explore bystander CPR and invited lay rescuers who had recently (ie, within 1 week) intervened in an OHCA to participate in semistructured interviews and focus groups. We used constant comparative analysis until theoretical saturation to derive a midrange explanatory theory of bystander CPR. We constructed a 3-stage theoretical model describing a common experiential process for lay rescuer intervention in OHCA: Being called to act is disturbing, causing panic, shock, and disbelief that must ultimately be overcome. Taking action to save the victim is complicated by several misconceptions about cardiac arrest, where victims are mistakenly believed to be choking, and agonal respirations are misinterpreted to mean the victim is alive. Making sense of the experience is challenging, at least in the short term, where lay rescuers have to contend with self-doubt, unanswered questions, and uncomfortable emotional reactions to a traumatic event. Conclusions: Our study suggests that current CPR training programs may not adequately prepare lay rescuers for the reality of an OHCA and identifies several key knowledge gaps that should be addressed. The long-term psychological consequences of bystander intervention in OHCA remain poorly understood and warrant further study.